Exploring the resident gut microbiota of stranded odontocetes: high similarities between two dolphin species Tursiops truncatus and Stenella coeruleoalba. (29th November 2020) - Abdelrhman, Khaled F. A.; Ciofini, Alice; Bacci, Giovanni; Mancusi, Cecilia; Mengoni, Alessio; Ugolini, Alberto
Abstract: The evaluation of symbiotic microbial communities occurring in the intestinal tract of animals has received great interest in recent years. However, little is known about gut microbial communities in cetaceans, despite their relevance in the ecology of marine communities. Here, we report an investigation using 16S rRNA gene amplicon sequencing of the resident gut microbiota of the two cetacean species Stenella coeruleoalba and Tursiops truncatus by sampling intestinal mucosa from specimens retrieved stranded along the Tyrrhenian coast of Tuscany (Italy). We found an abundance of members from Clostridiaceae and Fusobacteriaceae, which in total accounted for more than 50% of reads, in agreement with gut microbiota composition of other carnivorous mammals. Probably due to the limited number of samples available, sex, preservation status and also species, did not correlate with overall differences in the microbiota. Indeed, a high similarity of the taxonomic (family-level) composition between the gut microbiota of the two species was found. However, Pedobacter spp. was found abundant in amplicon sequencing libraries from S. coeruleoalba, while clostridia were more abundant from T. truncatus samples. Our results shed some light on the gut microbiota composition of two dolphin ( S. coeruleoalba and T. truncatus ) species, with specimens collected in the wild. Studies with a larger number of individuals are now needed to confirm these first results and evaluate the interspecific differences in relation to sex and age.